The Libyan civil conflict: selected case series of orthopaedic trauma managed in Malta in 2014. Issue 1 (December 2015) - Ng, Colin; Mifsud, Max; Borg, Joseph; Mizzi, Colin
Abstract Aim The purpose of this series of cases was to analyse our management of orthopaedic trauma casualties in the Libyan civil war crisis in the European summer of 2014. We looked at both damage control orthopaedics and for case variety of war trauma at a civilian hospital. Due to our geographical proximity to Libya, Malta was the closest European tertiary referral centre. Having only one Level 1 trauma care hospital in our country, our Trauma and Orthopaedics department played a pivotal role in the management of Libyan battlefield injuries. Our aims were to assess acute outcomes and short term mortality of surgery within the perspective of a damage control orthopaedic strategy whereby aggressive wound management, early fixation using relative stability principles, antibiotic cover with adequate soft tissue cover are paramount. We also aim to describe the variety of war injuries we came across, with a goal for future improvement in regards to service providing. Methods Prospective collection of six interesting cases with severe limb and spinal injuries sustained in Libya during the Libyan civil war between June and November 2014. Conclusions We applied current trends in the treatment of war injuries, specifically in damage control orthopaedic strategy and converting to definitive treatment where permissible. The majority of our cases were classified as most severe (Type IIIB/C) according to the Gustilo-Anderson classification of open fractures. The injuries treated reflected the type of standard and improved weaponry available in modern warfare affecting both militants and civilians alike with increasing severity and extent of damage. Due to this fact, multidisciplinary team approach to patient centred care was utilised with an ultimate aim of swift recovery and early mobilisation. It also highlighted the difficulties and complex issues required on a hospital management level as a neighbouring country to war zone countries in transforming care of civil trauma to military trauma.